Analisis Pengaruh Program Keluarga Harapan dalam Mengurangi Pekerja Anak di Indonesia - Bunda, Mutiara; N, Zulkifli (Jurnal Informatika Ekonomi Bisnis, 2025)
This study examines the impact of the Program Keluarga Harapan, a conditional cash transfer initiative, on reducing child labor in Indonesia. Using a quantitative approach, the research employs logistic regression analysis on data from the 2022 National Socio-Economic Survey. The findings reveal that PKH significantly reduces the likelihood of child labor by 0.383 times, demonstrating its effectiveness in reallocating children's time from work to education. Additionally, factors such as child age, gender, household head characteristics, and rural residence significantly influence child labor prevalence. The study highlights the need for expanded program coverage, improved rural education access, and multi-sector collaboration to address the root causes of child labor.